KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH DALAM MEMBANGUN BUDAYA ORGANISASI MADRASAH DI MTS AN NAJAH PEKANBARU - Instiyawati Hakim; Sherly Indriani; Winda Aprilia (STKIP Pesisir Selatan, 2026)
This study aims to analyze the transformational leadership of the principal at MTs An Najah Pekanbaru in developing the school’s organizational culture. A qualitative descriptive approach was employed, using in-depth interviews, participatory observation, and document analysis, including the school’s vision, mission, motto, and work programs. Data were analyzed thematically to identify leadership characteristics, strategies implemented, and the resulting organizational culture. The findings indicate that the principal exhibits strong transformational leadership, characterized by moral exemplarity, the ability to build and communicate a clear vision, inspirational communication, and the empowerment of teachers and educational staff. Strategies applied include internalizing the vision and mission, continuous coaching, participatory deliberation, role modeling, and effective communication, which collectively foster a harmonious work climate. This leadership style has cultivated an organizational culture that is religious, inclusive, participatory, disciplined, professional, and adaptive, enhancing a sense of ownership, loyalty, and commitment among school members. The study confirms that transformational leadership is a key factor in developing a robust organizational culture that supports harmonious performance at MTs An Najah Pekanbaru. These findings provide valuable implications for leadership development and the strengthening of organizational culture in Islamic educational institutions.